Role of Macrophages in the Pathogenesis of Atopic Dermatitis. (4th March 2013) - Kasraie, Sadaf; Werfel, Thomas
Abstract : Atopic dermatitis (AD) is one of the most common and most intensively studied chronic inflammatory skin diseases. Several cofactors, such as an impaired skin barrier function, modifications of the immune system, and a complex genetic background, direct the course of AD. Within this complex network, macrophages play a pivotal role in enhanced susceptibility to cutaneous infections and act as central connecting components in the pathogenesis of AD on the cellular level. In AD, macrophages are known to accumulate in acutely and chronically inflamed skin. During the early and short inflammatory phase, macrophages exert proinflammatory functions like antigen-presenting phagocytosis and the production of inflammatory cytokines and growth factors that facilitate the resolution of inflammation. However, persistence of pro-inflammatory activity and altered function of macrophages result in the development of chronic inflammatory diseases such as AD. The exact mechanism of macrophages activation in these processes is not yet completely understood. Further studies should be performed to clarify the dysregulated mechanism of macrophages activation in AD, and this would allow us to target these cells with versatile functions for therapeutic purpose and improve and control the disease. In this paper, we highlight the new findings on dysregulated function of macrophages and the importance of these cells in the pathogenesis of AD in general and the contribution of these cells in enhanced susceptibility against microbial infections in particular.